Identification of Yield-Limiting Factors in Southeast Kansas Cropping Systems - G. F. Sassenrath; X. Lin; D. E. Shoup (Kansas Agricultural Experiment Station Research Reports, 2015)
Crop performance and yield within production fields varies as a function of growing environment and soil properties within the field. Components contributing to yield in corn, wheat, and soybean production were examined through on-farm measurements of soil properties in southeast Kansas. Additional tests in research plots explored components contributing to yield in greater detail. Environmental variability between the 2013 and 2014 growing seasons contributed to differences in yield. Additional variability in soil parameters influenced crop performance, particularly for soils high in clay content.
Keywords: yield-limiting factors; cropping systems; southeast Kansas; corn; wheat; soybean